ANALISIS WACANA KEKERASAN SEKSUAL TERHADAPA PEREMPUAN - Della Sofia; Reza Aprianti; Eraskaita Ginting (Jurnal Prodi Ilmu Komunikasi, 2022)
Sexual violence that often occurs in Indonesia at this time is very worrying, many victims of sexual violence are afraid to report this heinous act to those who really regulate cases of sexual violence and most of the survivors of this sexual violence are women. In Indonesia, sexual violence is already very worrying. It can happen anywhere and anytime. The number of victims is increasing and the perpetrators of this violence can be from those closest to them. Various kinds of online mass media such as Tempo.co and sonora.id which are online magazines and newspapers that often bring news about cases of sexual violence to public spaces. This research was conducted with the aim of finding out how online media coverage, especially in the magazines Tempo.co and Sonora.id, discusses sexual violence against women on their news portals. This study uses qualitative research methods and uses Sara Mills' theory which is related to feminism related to women such as sexual violence and how actors from subject-object and writer-reader positions will be written. From the results of the research, the position of the subject-object is how the event or event can be seen and from whose perspective the event can be seen, while the position of the writer-reader is how the position of the actor is displayed in the text that is displayed.